IMPACTS OF CLASSROOM’S MOBILE LEARNING: CAN SMARTPHONE SUPPORT STUDENTS’ COLLABORATION? - Didik Rinan Sumekto; Riyanto Riyanto; Avin Fadilla Hilmi; Nursyabani Purnama (English Review: Journal of English Education, 2019)
The trend of facilitating technological devices for students in the classroom still becomes controversial among teachers, whether these devices can be effectively applied or conversely. This study aims at revealing students’ collaboration effectiveness using smartphones. 528 teachers of primary and secondary schools in Sleman District, Indonesia involved as the respondents. Data collection used self-rated questionnaire indicating teachers’ perceptions and was analyzed by descriptive and factor analysis tests. The results confirmed that learning and discussion with peer, comfortableness with learning activity, dynamic learning atmosphere, mutual appreciation when giving feedback, mutual respect with peer, and collective usage encourages a good habit of learning descriptively engaged students’ collaboration effectiveness, whereas one factor, peer’s social relationships with teachers gain better showed its ineffectiveness. Further, the principal component sequentially adjudged the position of seven perceived factors with the Eigenvalue and the factorial analyses affirmed two rooted components with a total factor of 72.97%, where component 1 gained 67.16% and component 2 gained 5.81%. Using smartphones coherently need an exploration and an engagement through the social mechanism to support students’ learning activities.